Analysis of Students’ Academic Literacy Skills: A Pilot Study on The Development of A Scientific Writing Module Based on Douglas Walton’s Witness Arguments - Nesi, Antonius; Rokhman, Fathur; Rustono, Rustono; Pristiwati, Rahayu (Universitas Negeri Semarang, 2025)
Academic literacy encompasses all literacy practices, including the scientific writing skills. This sort of writing requires critical, analytical, and evaluative thinking skills, which are closely linked to the construction of arguments within academic texts. This study aims to analyze students’ academic literacy skills as a pilot study for the development of an instructional module on scientific writing based on argumentation. The type of argumentation used in this study is the witness argument model proposed by Douglas Walton. A qualitative approach was employed through document study. The data sources for this research included the course syllabus and students’ journal article manuscripts. Content analysis was used for data analysis, involving procedures of data collection, reduction, and verification. The research findings are described as follows. First, the Academic Literacy course syllabus was designed to incorporate three competencies at the lower taxonomy levels (C1 and C2), four competencies at the medium levels (C3 and C4), and seven competencies at the higher levels (C5 and C6). Second, the representation of the witness argument type in students’ journal articles included expert opinion arguments, analogy arguments, practical reasoning arguments, fact-hypothesis arguments, exception arguments, and precedent arguments. The results of this pilot study may serve as a foundation for further research, particularly in the development of an instructional module for scientific writing based on the witness argument model.